Social Layer In the Development of Civil Society - Okyulov Hasan Omonbaevich, (European Journal of Life Safety and Stability (2660-9630), 2023)
The article analyzes the trends in the growth of the middle social class in the societies of developed countries, their role in the development and improvement of civil society, the significance of the experience of Western countries in this area for Uzbekistan. Also, the readers are offered the reforms carried out in Uzbekistan in this area, and their results